Complementary split ring resonator sensors for dielectric characterization of liquids in biosensing applications - Jonathan Farrugia; Joseph Caruana; Iman Farhat; Julian Bonello; Charles Sammut (Sensing and Bio-Sensing Research, 2025)
This study explores the design, optimization, and experimental validation of complementary split ring resonators (CSRR) for dielectric characterization of liquids, with a focus on biosensing applications. Six CSRR configurations featuring circular geometries with capacitance-enhancing modifications were evaluated. A particle swarm optimization algorithm was employed to maximize sensitivity, quality factor, and resonant peak magnitude. Experimental testing used saline solutions with varying bovine serum albumin concentrations, mimicking the electrical properties of blood. Among the designs, the Meandered Capacitance Single Ring (MC-SR) resonator emerged as the most effective, demonstrating high sensitivity and consistent results. Close alignment between simulations and experiments validated the sensor’s capability to detect subtle dielectric variations within the liquid under test across the 1.5–3 GHz range. Preliminary simulations indicate that the MC-SR CSRR achieves sufficient penetration depth to detect changes beneath skin and subcutaneous fat layers with a combined thickness of 1.5 mm. These findings highlight the potential of CSRR-based sensors for non-invasive biosensing applications, such as monitoring glucose levels and other blood analytes, by effectively addressing sensitivity challenges while only partially improving selectivity. Future efforts will aim to refine on-body sensing applications and enhance robustness in real-world scenarios, with a particular focus on overcoming selectivity limitations.